A Review on Emerging Trend of Medical Armour - Nanorobot - Gupta, Aparna; Singh, Lalit (Current Nanomaterials, 2021)
Background: Prevention and control of infected cell growth is the major task to work in the medical field and this enforces the formulary scientists to develop such dosage forms or devices that can eradicate such medical issues and provide ease to the patient. So, with this viewpoint, in the current scenario, scientists are working on such approaches, which can easily reach the suffering site to diagnose and treat such medical issues. Objective: This analytical work mainly aims towards assessing some approach, which assists the system to reach the suffering site easily and rapidly as well as work on the site for better therapeutic benefit. This may be achieved by developing a nanorobot, which is the finest nanotechnology that can act as a medical armor for fighting against dreadful diseases like cancer. Methods: It is able to deal at a molecular level with precision at nanoscale measurement. They are often known by the name nanomedicines, which can deliver the payload (drug) at the site of action. Results: Nanorobot offers a number of advantages over present methods of drug delivery like improved bioavailability, targeting the site of action, fewer surgeon mistakes, and capable of reaching out to devious areas of the body. Nanorobots are manufactured with the complete integration of onboard sensors, power supplies, motors, manipulators, and molecular computers. Their generation was originated from the idea of carbon nanotubes. Conclusion: Nanorobot may bring up a new era in the field of nanotechnology. So, nanorobots are emerging as a beneficial tool for the treatment of various human diseases and are bringing improvement in the human biological system.
Keywords: nanorobot control design (NCD)